Activation of the Liver X Receptor Inhibits Th17 and Th1 Responses in Behcet’s Disease and Vogt-Koyanagi-Harada Disease - Wu, L.; Wen, H.; Zhou, Y.; Yu, H.; Liu, Y.; Bai, L.; Kijlstra, A.; Yang, P. (Current Molecular Medicine, 2014)
Behcet’s disease (BD) and Vogt-Koyanagi-Harada (VKH) syndrome are two intraocular inflammatory diseases that are caused by an aberrant T lymphocyte response. Th17 cells, mainly producing the cytokine IL-17, and Th1 cells, characterized by the production of the index cytokine IFN-γ, are the CD4+ T lymphocyte subsets implicated in the pathogenesis of both BD and VKH. Suppressing the excessive response of these Th17 and Th1 cells has been reported to be an effective therapeutic approach to treat these patients and continuous efforts are being undertaken to find new methods to modulate the function of these cells. Evidence is emerging that the Liver X receptor (LXR) is an important regulator of inflammatory and immune responses and the study reported here was designed to investigate the role of LXR activation in BD and VKH. Here we demonstrate that the frequency of Th17 and Th1 cells along with the relevant cytokines IL-17, IFN-γ and corresponding transcriptional factors RORC, T-bet were all decreased following LXR activation by the agonist GW3965. LXR controlled the expression of inflammatory cytokines through an effect on NF-kappa B (NFκb) phosphorylation. Data from our study provide evidence for an association between a decreased LXR expression and disease activity in both BD and VKH, due to the fact that a lower LXR activation may result in an enhanced Th1 and Th17 immune response. Our study suggests that enhancing LXR activation may offer a potential therapeutic approach targeting aberrant immune responses by inhibiting Th1 and Th17 cell responses.
Keywords: Th1